2013
DOI: 10.1186/1471-5945-13-15
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and hepatic effects of vascular epidermal growth factor (VEGF) used to stimulate hair growth in an animal model

Abstract: BackgroundAlopecia areata is the hair loss usually reversible, in sharply defined areas. The treatment of alopecia using growth factors shows interesting activity in promoting hair growth. In this concept, VEGF (vascular endothelial growth factor) is a marker of angiogenesis, stimulating hair growth by facilitating the supply of nutrients to the hair follicle, increasing follicular diameter. The aim of this study was the evaluation of a topical gel enriched with VEGF liposomes on the hair growth stimulation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 12 publications
1
25
1
1
Order By: Relevance
“…This is believed to increase the flow of necessary nutrients to the hair and thus promotes hairgrowth. 17,18 However, the results showed that the difference was not found to be significant. The lack of a significant difference for minoxidil is likely to be associated with the culture conditions or individual differences of the donors of the HDPC.…”
Section: Discussioncontrasting
confidence: 41%
“…This is believed to increase the flow of necessary nutrients to the hair and thus promotes hairgrowth. 17,18 However, the results showed that the difference was not found to be significant. The lack of a significant difference for minoxidil is likely to be associated with the culture conditions or individual differences of the donors of the HDPC.…”
Section: Discussioncontrasting
confidence: 41%
“…Furthermore, TB4 accelerates hair growth via activation, migration, and differentiation of hair follicle stem cells [ 38 , 41 ]. Recently, VEGF was shown to stimulate hair growth by facilitating the supply of nutrients to the hair follicle, increasing the follicular diameter [ 42 , 43 ]. Based on these reports, TB4 and VEGF are regarded as the main factors in the hair growth promotion effect of the CM of LL-37-activated ASCs.…”
Section: Discussionmentioning
confidence: 99%
“…As for anti‐angiogenic therapy in clinical application with chemotherapy, bevacizumab, an anti‐VEGF antibody, has been reported to decrease vascular permeability 24,25 and VEGF to enhance it 26 . VEGF is also known as one of the hair growth factors, 27 and it has been reported that VEGF itself and a component that activates VEGF are effective as a therapeutic agent for alopecia areata, non‐scarring alopecia, and androgenic alopecia 28‐30 . Although there have been no reports of association between anti‐VEGF antibody and CIA, it is reported that hair loss was more frequent in a bevacizumab‐plus regimen than in a regimen without bevacizumab (67% vs 48%) in a clinical trial 31 .…”
Section: Discussionmentioning
confidence: 99%